Tunability of a red-shifted free electron laser - Marie Labat; Eléonore Roussel; Philippe Berteaud; Frédéric Blache; Yen-Yu Chang; Jurjen Couperus Cabadağ; Amin Ghaith; Maxwell LaBerge; Stéphane Lê; Susanne Schöbel; Ulrich Schramm; Patrick Ufer; et al. (Physical Review Accelerators and Beams, 2025)
The development of red-shifted free electron lasers (FELs), based on strongly chirped electron beams, emerged a few years ago. Here we present a thorough study of the tunability of a seeded red-shifted FEL. An analytical model is introduced to describe the complex FEL resonance condition and its consequence for the FEL emission wavelength. This model is then benchmarked with experimental data from the COXINEL (COherence Xray source INferred from Electrons accelerated by Laser) FEL beamline driven by a laser plasma accelerator at Helmholtz-Zentrum Dresden-Rossendorf. We show that the FEL emission wavelength can be tuned not only with the undulator gap and taper geometry but also with the time delay between the seed laser pulse and the electron beam. Particularly a combination of individually chirped electron and seed beams promotes a wider tuning range compared with the usual undulator gap. This could serve as an additional yet simple tuning knob to tailor the FEL emission wavelength.